Utilization of the S.Id Microsite Platform in Improving the Quality of Education at State Elementary School - Nurhidayati, Evi; Rosadi, Kemas Imron; Yusria, Yusria (Al-Qalam Institue, 2025)
State Elementary School has adopted the S.Id Microsite Platform as part of efforts to improve education quality through digital-based learning. This platform serves to accelerate the dissemination of information, expand access to learning materials, and enhance communication among school stakeholders. This study employed a qualitative descriptive method with principals, teachers, and students as research subjects. Data were collected through interviews, observation, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. The findings show that the utilization of the S.Id Microsite follows structured stages, starting with preparation and training, and continuing with daily use in teaching and learning. Its implementation is supported by strong school commitment, adequate infrastructure, and the platform’s ease of access and communication features. However, challenges remain, including unstable internet connectivity, limited digital literacy among some teachers and students, as well as device shortages and time management constraints. To address these obstacles, schools need to improve technology access, strengthen digital literacy, and manage the platform more effectively. Overall, the S.Id Microsite has contributed positively to learning innovation and provides a promising step toward the digitalization of education at the elementary school level.